Invasive vascular plant species of oxbow lakes in south-western Poland - Spałek, Krzysztof (Biodiversity: Research and Conservation, 2015)
Natural water reservoirs are very valuable floristic sites in south-western Poland. Among them, the most important for the preservation of biodiversity of flora are oxbow lakes. The long-term process of human pressure on habitats of this type caused disturbances of their biological balance. Changes in the water regime, industrial development and chemisation of agriculture, especially in the period of the last two hundred years, led to systematic disappearances of localities of many plant species connected with rare habitats and also to the appearance of numerous invasive plant species. They are: Azolla filiculoides, Echinocystis lobata, Erechtites hieraciifolia, Impatiens glandulifera, I. parviflora, Reynoutria japonica, Solidago canadensis, S. gigantea and S. graminifolia. Field works were conducted in years 2005-2012.